(untitled) (ENTHYMEMA, 2025)
This paper explores the intersection of poetic form and transnational identity in contemporary women’s poetry, focusing on the strategic use of fragmentation and prose poetry. By examining the works of poets Don Mee Choi, Emily Jungmin Yoon, and Cathy Park Hong, it highlights how these forms enhance the exploration of spatiotemporal experiences and cultural belonging. I show how the interplay between fragmented poetry and prose poetry creates a dynamic aesthetic, reflecting the layered complexity of lived experiences, trauma, and resilience. Through a detailed analysis, this paper demonstrates how the use of prose poetry provides a versatile platform for delving into narratives of confinement and oppression, while fragmented forms capture the fluidity and dislocation inherent in transnational identities. I highlight how the integration of personal and socio-political narratives underscores the interconnectedness of global experiences, offering new perspectives on identity and belonging in a constantly shifting world.